Evaluation of combining abilities of new sunflower inbred lines - Ćirić Mihajlo; Jocić Siniša; Cvejić Sandra; Čanak Petar; Jocković Milan; Marinković Radovan; Mirosavljević Milan (Ratarstvo i Povrtarstvo, 2013)
Days to flowering, plant height and head diameter are significant parameters which are directly or indirectly correlated with yield, main trait of sunflower. Eight CMS lines, three testers and their twenty four hybrids were examined by line x tester method. Significant differences were found between lines, testers and hybrids. Results showed that lines PD-3 and PD-25 had good combining abilities for the trait of days to flowering (58 days and 65 days, respectively). In the expression of plant height best combiners were PD-2 (107.5 cm) and PD-3 (108.7 cm). For head diameter lines PD-52 (24.5 cm) and MA-57 (23.2 cm) were marked as good combiners. Variance of SCA was greater than variance of GCA for all the traits. CMS lines had the greatest part in the expression of the analyzed traits. Non-additive type of gene effect was reported for all examined traits, which implies that they could be improved through heterosis breeding.